Skepticism of Students Participating in National Science Olympiad in Solving Geometry Problems across Gender Differences - Orrissa, Rahmadina Dwi; Suwarno, Suwarno (FKIP Universitas Lampung, 2024)
This study is a qualitative descriptive study that aims to determine and describe the skeptical attitudes of female and male students involved in solving logical problems in geometry material and identify differences in problem-solving strategies between them. The researcher refers to the skeptical stages developed by Berta (2024) which consist of two stages, namely skepticism confirming and skepticism dismissing. This study involved two tenth grader female students and two eleventh grade male students participating in national science olympiad from MAN 1 Jembrana, Indonesia. The data analysis techniques in this study were data reduction, data presentation, and drawing conclusions or verification. Data collection used in this study was in the form of Logical problems-III questions, interviews and the think aloud method. The findings of this study indicate that there are significant differences between the ways male and female national science olympiad students deal with illogical questions. Male national science olympiad students tend to show higher skepticism, characterized by a tendency to dismiss work and calculations without alternative solutions. In contrast, female national science olympiad students tend to use a more careful and systematic approach to solving problems and are more careful in questioning the information provided and getting alternative solutions that result in more systematic solutions. Although this sometimes causes confusion or doubt that can slow down the decision-making process but can get calculated results. This study concludes that gender differences in skepticism affect students' approaches to solving Logical problems-III which emphasizes the importance of adaptive learning strategies to support the development of critical and logical thinking skills in both groups of students. Keywords: geometri,logical problems-iii, skeptis. DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp496-511